2022 Award as ‘Distinguished Collaborator’ of Lodz University of Technology - Fotopoulos, Vasileios (My University, 2026)
I received an award by the TUL Rector in a special ceremony as a Distinguished Collaborator of Lodz University of Technology
Keywords: Natural sciences